PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Kharisma Aulia Dianitha; Endang Masitoh; Purnama Siddi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT The purpose of this study is to determine the effect of financial ratios on profit growth in the food and beverage sub-sector manufacturing companies. The variables in this study are Quick ratio (QR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Return on Investment (ROI). Sampling uses a purposive sampling technique with certain criteria. Which produced a sample of 12 food and beverage companies listed on the Indonesia Stock Exchange in 2015-2018. The analysis in this study uses multiple linear regression analysis by showing the results that Quick Ratio, Debt to Equity Ratio, Net Profit Margin has no effect on earnings growth, while Return On Investment has an effect on earnings growth. Key Words: QR, DER, NPM, ROI, Growth Profits